ANALISIS TERHADAP TINDAK PIDANA PENGANGKUTAN LIMBAH BAHAN BERBAHAYA DAN BERACUN (Studi Pada Putusan Pengadilan Negeri Pati Nomor: 8/PID.Sus/2015/ PN Pti) - NUGROHO, INDRIATI (Dinamika Hukum, 2018)
The purpose of this study is to: 1) analyzes the legal consideration of judges in meting out the verdict against the criminal acts of the transport of waste hazardous toxic ingredients on the ruling of the District Court of starch number: 8/PID. SUS/2015/PN Pti. 2) Analyze criminal law enforcement perpetrators of criminal acts of hauling B3 already oriented to embody aspects of Justice. The method of approach in writing this is the juridical normative. The specification of this research uses descriptive analytic. Data source using data skunder. Engineering data collection using the study of librarianship and study documents. To analyze the data, the researchers used a qualitative normative method. Based on the research results obtained the conclusion that legal Considerations: 1) judge in meting out the verdict against the criminal acts of the transport of waste hazardous toxic ingredients on the ruling of the District Court of starch number: 8/PID. SUS/2015/PN Pti IE in the form of imprisonment for 1 (one) year and a criminal fine of Rp. 1,000,000,000 (one billion dollars) to the provisions if the defendant does not pay criminal fines that will be replaced by criminal confinement for: 2 (two) According to the author of the Moon is just right. The Tribunal judge in disconnected things already consider the facts in the trial as well as the evidence presented by the Prosecutor in the trial proceedings. 2) law enforcement criminal perpetrators of criminal acts of hauling B3 oriented to embody aspects of Justice should pay attention to three basic values in the enactment of the law in the community, that is based on fairness, expediency, and legal certainty. Philosophical aspects of Justice, sociological benefit/usefulness, then legal certainty concerning the juridical side. In the above case, according to the authors of the justice aspect-oriented yet because of social or economic aspectsbased who intervened by law and law enforcement are not balanced, equal treatment was not performed against the same offender. The verdict is only fulfilling aspects of positive law but does not provide fairness and expediency. The law goes into effect is the law in favor of no law above the parties. So the legal products issued a legal product is not equitable. Keywords: Criminal Act of Transportation, Waste Hauling Hazardous Toxic Materials